Floristic and structural analysis of tropical forest in Palo Verde National Park, Costa Rica - Rodríguez-González, Elia Anahí (2026)
Costa Rica has increased its tree canopy cover; however, deforestation and forest degradation still persist. Tropical forests are globally scarce ecosystems and are particularly vulnerable to wildfires and other degradation factors. The use of advanced technologies such as remote sensing, combined with field inventory data, is essential to optimize measurements and generate reliable information to guide restoration and conservation actions. This study presents findings on the floristic composition and forest structure of Palo Verde National Park. The data were analyzed based on biomass classes estimated through allometric equations, as part of a broader research project that also includes two additional sites within the North Pacific Ecoregion. The information obtained will serve as a foundation for developing a new statistical model for estimating aboveground biomass in tropical forests. For this study, 30 plots of 500 m² were established using a high-precision GNSS receiver (RTK). All trees with a diameter ≥ 5 cm were measured, along with total height. The relative sampling error was 11.48%, with an average density of 1,168 individuals ha-¹ and a mean basal area of 17.84 m² ha-¹. Aboveground biomass estimated using allometric equations ranged from 46.43 Mg ha-¹ to 141.77 Mg ha-¹. The most structurally important species, according to the Importance Value Index (IVI), were Luehea candida, Guazuma ulmifolia, and Calycophyllum candidissimum.